Malcolm X at Oxford Union : racial politics in a global era - Ambar, Saladin M. (Transgressing boundaries., 2014)
"In 1964 Malcolm X was invited to debate at the Oxford Union Society at Oxford University. The topic of debate that evening was the infamous phrase from Barry Goldwater's 1964 Republican Convention speech:"Extremism in the defense of liberty is no vice; moderation in the pursuit of justice is no virtue." At a time when Malcolm was traveling widely and advocating on behalf of blacks in America and other nations, his thirty minute speech at the Oxford Union stands out as one of the great addresses of the civil rights era"--